A Historical Study of Law in Precolonial Asante (1700-1896) - Ayamdoo, Mathew Awine (African historical review, 2024)
The use of regulations, rules, norms, taboos, tradition and the like to regulate human behaviour and the relationship between humans and their society has been in existence since time immemorial. The dominant narrative in the legal history of Africa is that precolonial African societies lacked organised legal systems as there was no organised law and order in most precolonial African societies. This study challenges this dominant narrative by historically examining the nature of law and the legal regime in precolonial Asante from 1700-1896. The study contributes to the existing body of knowledge by unravelling the existence and nature of a strong legal system in the form of customary law in precolonial Asante within the period specified. This qualitative study adopted a desktop review approach and a historical research design to trace the nature of law and the legal regime in precolonial Asante. The study traces the formation of the Asante kingdom to 1700 and how law was administered until the kingdom was annexed by the British colonial authorities in 1896. The study argues strongly that, despite its shortcomings, there existed a very strong legal regime in Asante which made good use of customary law in almost every aspect of life years before the introduction of colonialism by the British.